The Influence of Cultural Sentiment and Parental Intervention on the Political Participation of Young Voters Among Students - Alhuda Firman Paringja; Risma Margaretha Sinaga; Muhammad Mona Adha (International Journal of Educational and Life Sciences, 2025)
This study aims to analyze the influence of cultural sentiment and parental intervention on the political participation of young voters in Indonesia. The study uses a descriptive verification method with an ex post facto and survey approach. Data were collected from 51 young voters who have the right to vote in the 2024 General Election. The results of the study show that cultural sentiment and parental intervention do not have a significant individual influence on the political participation of young voters. This suggests that other factors may be more dominant in influencing the political participation of young voters. This research makes an important contribution to understanding the factors that influence the political participation of young people in Indonesia.